Genome-Wide Expression Profiling of Anoxia/Reoxygenation in Rat Cardiomyocytes Uncovers the Role of MitoKATP in Energy Homeostasis. (15th June 2015) - Cao, Song; Liu, Yun; Sun, Wenting; Zhao, Li; Zhang, Lin; Liu, Xinkui; Yu, Tian
Abstract : Mitochondrial ATP-sensitive potassium channel (mitoK ATP ) is a common end effector of many protective stimuli in myocardial ischemia-reperfusion injury (MIRI). However, the specific molecular mechanism underlying its myocardial protective effect is not well elucidated. We characterized an anoxia/reoxygenation (A/R) model using freshly isolated adult rat cardiomyocytes. MitoK ATP status was interfered with its specific opener diazoxide (DZ) or blocker 5-hydroxydecanote (5-HD). Digital gene expression (DGE) and bioinformatic analysis were deployed. Three energy metabolism related genes ( MT-ND6, Idh2, and Acadl ) were upregulated when mitoK ATP opened. In addition, as many as 20 differentially expressed genes (DEGs) were significantly enriched in five energy homeostasis correlated pathways (PPAR, TCA cycle, fatty acid metabolism, and peroxisome). These findings indicated that mitoK ATP opening in MIRI resulted in energy mobilization, which was confirmed by measuring ATP content in cardiomyocytes. These causal outcomes could be a molecular mechanism of myocardial protection of mitoK ATP and suggested that the mitoK ATP opening plays a physiologic role in triggering cardiomyocytes' energy homeostasis during MIRI. Strategies of modulating energy expenditure during myocardial ischemia-reperfusion may be promising approaches to reduce MIRI.